2009
DOI: 10.1186/1472-6785-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of feral horses on a desert environment

Abstract: BackgroundFree-ranging horses (Equus caballus) in North America are considered to be feral animals since they are descendents of non-native domestic horses introduced to the continent. We conducted a study in a southern California desert to understand how feral horse movements and horse feces impacted this arid ecosystem. We evaluated five parameters susceptible to horse trampling: soil strength, vegetation cover, percent of nonnative vegetation, plant species diversity, and macroinvertebrate abundance. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Horses are very different to Australian native animals because they are large, hoofed and graze congregationally; therefore they change the landscape by destroying grasses that are intolerant to heavy grazing Dobbie et al 1993). Vegetation destruction causes reduction in biodiversity through loss of natural shelters and food sources for communities of amphibians, reptiles, birds and small mammals (Wharton and Dempster 1981;Ostermann-Kelm et al 2009). In mountainous areas, feral horses deplete water supplies, and contaminate water with faeces Dawson et al 2006).…”
Section: Impact Of Feral Horses In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…Horses are very different to Australian native animals because they are large, hoofed and graze congregationally; therefore they change the landscape by destroying grasses that are intolerant to heavy grazing Dobbie et al 1993). Vegetation destruction causes reduction in biodiversity through loss of natural shelters and food sources for communities of amphibians, reptiles, birds and small mammals (Wharton and Dempster 1981;Ostermann-Kelm et al 2009). In mountainous areas, feral horses deplete water supplies, and contaminate water with faeces Dawson et al 2006).…”
Section: Impact Of Feral Horses In Australiamentioning
confidence: 99%
“…In some national parks, stripping leaves and chewing bark can result in destruction of eucalyptus NSW National Parks and Wildlife Service 2007). In semi-arid and arid areas, feral horses accelerate erosion by compacting soil and denuding plant cover Dobbie et al 1993;Ostermann-Kelm et al 2009). …”
Section: Impact Of Feral Horses In Australiamentioning
confidence: 99%
“…Feral horses (Equus caballus) can be found on every continent of the earth except Antarctica [6], and have an impact on soil and vegetation [7,8], the biodiversity of plants [9], and several animal species, such as reptiles and small mammals [10,11], ants [7], herbivores [12,13] and grassland birds [14]. Nevertheless, among the genus Equus itself, great diversity can be observed [15].…”
Section: The Horse-environment Relationshipmentioning
confidence: 99%
“…The presence of wild horses leads to a significant reduction of the desert bighorn sheep and elks sharing the same water source, which is evidence of indirect competition [12,13]. Wild horses can have a negative impact on environmental health, for example horses' trampling leads to an increased soil strength and compaction, which reduces rainwater infiltration [8]. This in return can lead to nutrient and water shortages for plants and trees.…”
Section: The Horse-environment Relationshipmentioning
confidence: 99%
“…Horse grazing promotes plants with low nutrient requirements and robust defense strategies (Catorci et al 2012). However, the impacts of grazing by horses on arid environments are highly influenced by animal density and abiotic factors (Ostermann-Kelm et al 2009). Whereas biogeography and abiotic factors may show a greater influence than horse grazing on variables such as percentage of vegetation cover and cover of key plant species (often highly palatable grasses; Fahnestock andDetling 1999, Beever et al 2003), numerous studies have reported impacts of horse grazing on nesting bird communities (Zalba and Cozzani 2004), reptile species richness and abundance (Beever and Brussard 2004), nonnative plant cover (Loydi and Zalba 2009), and disturbancesensitive variables, such as soil surface hardness and number of ant mounds .…”
mentioning
confidence: 99%